2022
DOI: 10.1002/cjoc.202200132
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Cross‐Coupling of Alkylzirconocenes and Aryl Chlorides

Abstract: Comprehensive Summary Alkylzirconocenes, readily prepared by hydrozirconation of alkenes with Schwartz's reagent, are perspective yet rarely exploited partners in transition‐metal catalyzed cross‐coupling reaction. The notoriously low nucleophilicity of alkylzirconocenes and the potential β‐H elimination restrict their application in cross‐coupling. Herein, we report the first Pd‐catalyzed aryl‐alkyl cross‐coupling of alkylzirconocenes and aryl halides. A commercially available N‐heterocyclic carbene (IPr) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…13 C NMR (101 MHz, CDCl 3 ) δ 142.5, 128.4, 128.2, 125.6, 35.8, 31.1. Spectroscopic data is consistent with the literature [34] …”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…13 C NMR (101 MHz, CDCl 3 ) δ 142.5, 128.4, 128.2, 125.6, 35.8, 31.1. Spectroscopic data is consistent with the literature [34] …”
Section: Methodssupporting
confidence: 90%
“…Spectroscopic data is consistent with the literature. [34] Gram Scale Synthesis of 3 a: To a flame dried 200 mL Schlenk flask was added Ni(acac) 2 (0.7 mmol, 179.9 mg), IMes • HCl (0.7 mmol, 238.7 mg), NaO t Bu (1.05 mmol, 100.8 mg) and E-1 a (7.0 mmol, 1.26 g), the flask was vacuumed and refilled with nitrogen three times. Then anhydrous toluene (70 mL), 2 a (28.0 mmol, 3.248 g) and H 2 O (7.0 mmol, 126 mg) was added with syringe under nitrogen atmosphere.…”
Section: 2-diphenylethane (3 A)mentioning
confidence: 99%
“…52 Jiang and Shi reported the first palladium-catalyzed crosscoupling reaction of aryl chlorides and alkyl zirconium reagents using C8 (Pd(i-Pr)(cin)Cl) to catalyze the C(sp 2 )-C(sp 3 ) coupling reaction. 140 One entry showed that the triflate group can be well tolerated in the system and preferentially reacted at the chloride with a 40% yield (Scheme 29).…”
Section: N-heterocyclic Carbene Catalystsmentioning
confidence: 99%
“…We recently developed an array of bulky yet flexible NHCs 14 and applied them to a range of Ni-catalysed transformations, including challenging cross-coupling reactions. 15 We felt that a sterically demanding NHC ligand could promote R. E. At the same time, the conformational flexibility, available through rotatable single bonds on the ligand, may benefit coordination to the metal center, as well as oxidative addition (O. A.)…”
Section: Introductionmentioning
confidence: 99%